Method of forecasting the conditionof radio-electronic situation of multiple systems in the conditions of uncertainty - Momit, Alexander (Національний технічний університет "Харківський політехнічний інститут", 2019)
The task of forecasting future values of the time series based on its previous values is the basis for planning in the economy, trade, energy and technical fields. Forecasting of a radio-electronic situation in the conditions of shortage of radio-frequency resource is a very important component of modern high-tech military conflicts, the transport basis of which are multi-antenna radio-emitting means. For this purpose, an analysis of the known methods of forecasting the radio-electronic situation is carried out in that article. It is established that nowadays there are many models of time series prediction, namely: regression and autoregressive models, neural network models, exponential smoothing models, Markov-based models, classification models, etc. Based on the above analysis, it is found that the most appropriate for use in the prediction problems of the electronic environment of multi-antenna communication systems are time series prediction methods, which are based on autoregressive models. The article proposes a technique for predicting the condition of the radio-electronic environment, which allows to increase the noise immunity of communication systems in the conditions of deliberate interference and the unsteady nature of the predicted process, in order to ensure electromagnetic compatibility and increase the efficiency of use of radio frequency resource by complexes. To solve the scientific problem, we use the general scientific methods of analysis and synthesis of complex technical systems, the theory of noise immunity of radio engineering systems and methods of mathematical modeling. It is advisable to use this technique while assessing the electronic environment and identifying measures to enhance the security of communications systems. The calculations show that the use of this method allows to reduce the error of the forecast by an average of 20%. It is advisable to practically implement the proposed methodology while developing software for programmable radio stations.

Завдання прогнозування майбутніх значень часового ряду на основі його попередніх значень є основою для планування в економіці, торгівлі, енергетиці та технічних галузях. Прогнозування радіоелектронної обстановки в умовах дефіциту радіочастного ресурсу є дуже важливою складовою сучасних високотехнологічних воєнних конфліктів, транспортною основою яких виступають багатоантенні радіовипромінюючі засоби. З цією метою в зазначеній статті про ведено аналіз відомих методів прогнозування радіо-електронної обстановки. Встановлено, що на сьогоднішній день існує безліч моделей прогнозування часових рядів, а саме: регресивні і авторегресійні моделі, нейромережеві моделі, моделі експоненціального згладжування, моделі на базі ланцюгів Маркова, класифікаційні моделі та іншi. На основі зазначеного аналізу встановлено, що найбільш доцільним для використання в задачах прогнозування радіоелектронної обстановки багатоантенних систем радіозв’язку є методи прогнозування часових рядів на основі авторегресійних моделей. У статті запропонована методика прогнозування стану радіоелектронної обстановки, що дозволяє підвищити завадозахищеність систем зв’я зку в умовах впливу навмисних завад та нестаціонарному характері процесу, що прогнозується, з метою забезпечення електромагнітної сумісності та підвищення ефективності використанні радіочастотного ресурсу комплексами зв’язку. Для вирішення наукового завдання використані загальнонаукові методи аналізу та синтезу складних технічних систем, теорії завадозахищеності радіотехнічних систем та методи математичного моделювання. Зазначену методику доцільно використовувати при оцінці радіоелектронної обстановки та визначення заходів, що спрямовані на підвищення завадозахищеності систем зв’язку. Розрахунки показують, що використання зазначеної методики дозволяє зменшити похибку прогнозу в середньому на 20%. Практично реалізувати запропоновану методику доцільно при розробці програмного забезпечення програмованих радіостанцій.
Методика прогнозування стану радіоелектронної обстановки багатоантенних систем в умовах невизначеності
Keywords: noise immunity; intentional interference; завадозахищеність; навмисні завади; нестаціонарність